Proactive marketing for new and experienced library directors : going beyond the gate count - Goldsmith, Melissa Ursula Dawn; Fonseca, Anthony J. (Kidlington, UK : Elsevier, 2014)
This book offers theoretical reasoning and practical advice to directors on how to better market the function of the library within and beyond the home institution. The aim of this text is to help directors, and ultimately, their librarians and staff get students and faculty back into the library, as a result of better articulation of the library's importance.
Includes bibliographical references and index.
Keywords: Academic libraries; Libraries and students; Libraries and scholars; Libraries and teachers; Academic libraries